Pengaruh Senam Tae Bo Terhadap Tingkat Obesitas di Desa Pandanan - Hidayat, Wanda, Dwi Rosella K, S.Fis.,Ftr.,M.Fis, Agus Widodo, S.Fis.,Ftr., M.Fis (2015)
Obesity in this decade becomes a serious issue around the world. Many diseases can come because of obesity. One of a method to reduce obesity is by doing physical activity such as aerobic sport. One of aerobic sport which can reduce the obesity is Tae Bo aerobic.This research use quasi experimental research with pre and post test without control group design approach. Sampling technique uses purposive sampling with inclusion and exclusion criteria. Measuring obesity level uses mass body index. The data analysis in this research uses non parametric test with wilcoxon test.There is the influence of Tae Bo aerobic on the decreasing level of obesity in Pandanan village